### Show Posts

This section allows you to view all posts made by this member. Note that you can only see posts made in areas you currently have access to.

### Topics - Anyue Huang

Pages: [1]
1
##### Quiz-5 / TUT0202 Quiz5
« on: November 01, 2019, 02:00:08 PM »
Verify that the given functions y 1and y2 satisfy the corresponding homogeneous equation, then find a particular solution of the given nonhomogeneous equation.
$$t^{2} y^{\prime \prime}-t(t+2) y^{\prime}+(t+2) y=2 t^{3}, t>0 ; y_{1}(t)=t, y_{2}(t)=t e^{t}$$

$$y_{1}(t)=t \quad y_{1}^{\prime}(t)=1 \quad y_{1}^{\prime \prime}(t)=0$$
$$-t(t+2)+(t+2) t=0$$
$$y_{2}(t)=t e^{t} \quad y_{2}^{\prime}(t)=e^{t}+t e^{t} \quad y_{2}^{\prime \prime}(t)=2 e^{t}+t e^{t}$$
$$t^{2}\left(2 e^{t}+t e^{t}\right)-t(t+2)\left(e^{t}+t e^{t}\right)+(t+2) t e^{t}=0$$

Hence, $y_{1}$ and $y_{2}$ satisfy the homogeneons equation
$$y^{\prime \prime}-\frac{t+2}{t} y^{\prime}+\frac{t+2}{t^{2}} y=2 t$$
\begin{aligned} w&=\left|\begin{array}{cc}{t} & {t e^{t}} \\ {1} & {e^{t}+\operatorname{te}^{t}}\end{array}\right|=t^{2} e^{t}\\ w_{1}&=\left|\begin{array}{cc}{0} & {t e^{t}} \\ {1} & {e^{t}+t e^{t}}\end{array}\right|=-t e^{t}\\ w_{2}&=\left|\begin{array}{cc}{t} & {0} \\ {1} & {1}\end{array}\right|=t \end{aligned}
\begin{aligned} y_{p}(t) &=t \int \frac{\left(-t e^{t}\right)(2 t)}{t^{2} e^{t}} d t+t e^{t} \int \frac{(t)(2 t)}{t^{2} e^{t}} d t \\ &=t \int-2 d t+2 t e^{t} \int \frac{1}{e^{t}} d t \\ &=t(-2 t)+2 t e^{t}\left(-e^{-t}\right) \\ &=-2 t^{2}-2 t \end{aligned}

2
##### Quiz-5 / TUT0202 Quiz5
« on: November 01, 2019, 09:57:46 AM »
Verify that the given functions y 1and y2 satisfy the corresponding homogeneous equation;
then find a particular solution of the given nonhomogeneous equation.
$$t^{2} y^{\prime \prime}-t(t+2) y^{\prime}+(t+2) y=2 t^{3}, t>0 ; y_{1}(t)=t, y_{2}(t)=t e^{t}$$

$$y_{1}(t)=t \quad y_{1}^{\prime}(t)=1 \quad y_{1}^{\prime \prime}(t)=0$$
$$-t(t+2)+(t+2) t=0$$
$$y_{2}(t)=t e^{t} \quad y_{2}^{\prime}(t)=e^{t}+t e^{t} \quad y_{2}^{\prime \prime}(t)=2 e^{t}+t e^{t}$$
$$t^{2}\left(2 e^{t}+t e^{t}\right)-t(t+2)\left(e^{t}+t e^{t}\right)+(t+2) t e^{t}=0$$

Hence, $y_{1}$ and $y_{2}$ satisfy the homogeneons equation
$$y^{\prime \prime}-\frac{t+2}{t} y^{\prime}+\frac{t+2}{t^{2}} y=2 t$$
\begin{aligned} w&=\left|\begin{array}{cc}{t} & {t e^{t}} \\ {1} & {e^{t}+\operatorname{te}^{t}}\end{array}\right|=t^{2} e^{t}\\ w_{1}&=\left|\begin{array}{cc}{0} & {t e^{t}} \\ {1} & {e^{t}+t e^{t}}\end{array}\right|=-t e^{t}\\ w_{2}&=\left|\begin{array}{cc}{t} & {0} \\ {1} & {1}\end{array}\right|=t \end{aligned}
\begin{aligned} y_{p}(t) &=t \int \frac{\left(-t e^{t}\right)(2 t)}{t^{2} e^{t}} d t+t e^{t} \int \frac{(t)(2 t)}{t^{2} e^{t}} d t \\ &=t \int-2 d t+2 t e^{t} \int \frac{1}{e^{t}} d t \\ &=t(-2 t)+2 t e^{t}\left(-e^{-t}\right) \\ &=-2 t^{2}-2 t \end{aligned}

3
##### Quiz-3 / TUT0202 Quiz3
« on: October 11, 2019, 02:00:30 PM »
Find a differential equation whose general solution is $y=c_{1} e^{-t / 2}+c_{2} e^{-2 t}$.

Then $r_{1}=-\frac{1}{2}, r_{2}=-2$ are two roots of the characteristic equation of the required differential equation.

so the characteristic equation should look like
\begin{aligned}\left(r+\frac{1}{2}\right)(r+2) &=0 \\(2 r+1)(r+2) &=0 \\ 2 r^{2}+5 r+2 &=0 \end{aligned}

which corresponds to the DE

$$2 y^{\prime \prime}+5 y^{\prime}+2 y=0$$

Pages: [1]